Compositional and morphological changes in water-induced early-stage degradation in lead halide perovskites - Chen, Shi (2020)
With tremendous improvements in lead halide perovskite-based optoelectronic devices ranging from photovoltaics to light-emitting diodes, the instability problem stands as the primary challenge in their development. Among all factors, water is considered as one of the major culprits to the degradation of halide perovskite materials. For example, CH3NH3PbI3 (MAPbI3) and CH(NH2)2PbI3 (FAPbI3) decompose into PbI2 in days under ambient conditions. However, the intermediate changes of this degradation process are still not fully understood, especially the changes in early stage. Here we perform an in-situ investigation of the early-stage MAPbI3 and FAPbI3 degradation under high water vapor pressure. By probing the surface and bulk of perovskite samples using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) and XRD, our findings clearly show that PbI2 formation surprisingly initiates below the top surface or at grain boundaries, thus offering no protection as a water-blocking layer on surface or grain boundaries to slow down the degradation process. Meanwhile, significant morphological changes are observed in both samples after water vapor exposure. In comparison, the integrity of MAPbI3 film degrades much faster than the FAPbI3 film against water vapor. Pinholes and large voids are found in MAPbI3 film while only small number of pinholes can be found in FAPbI3 film. However, the FAPbI3 film suffers from its phase instability, showing a fast α-to-δ phase transition. Our results highlight the importance of the compositional and morphological changes in the early stage degradation in perovskite materials.